Benefits of Antimicrobial Photodynamic Therapy as an Adjunct to Non-Surgical Periodontal Treatment in Smokers with Periodontitis: A Systematic Review and Meta-Analysis - Villafuerte, Kelly R. V.; Martinez, Cristhiam Jesus H.; Palucci Vieira, Luiz H. [UNESP]; Nobre, Atila V. (MDPI, 2023)
The objective of this study was to analyze evidence of the clinical and microbiological benefits of antimicrobial photodynamic therapy (aPDT) adjunctive to scaling and root planing (SRP) in smokers with periodontitis. Randomized clinical trials (RCTs) were included, through an electronic search in PubMed/MEDLINE, LILACS, Web of Science, and the Cochrane Library for articles published in English until December 2022. The quality of the studies was assessed using the JADAD scale and the risk of bias was estimated using the Cochrane Collaboration assessment tool. Of the 175 relevant articles, eight RCTs were included. Of these, seven reported clinical results and five microbiological results, with a follow-up time of 3–6 months. A meta-analysis was performed for the probing depth (PD) reduction and clinical attachment level (CAL) gain at 3 and 6 months. The weighted mean differences (WMDs) and 95% confidence intervals (CIs) were counted for the PD and CAL. The overall effect for the PD reduction at 3 and 6 months (WMD = −0.80, 95% CI = −1.44 to −0.17, p = 0.01; WMD = −1.35, 95% CI = −2.23 to −0.46, p = 0.003) was in favor of aPDT. The CAL gain (WMD = 0.79, 95% CI = −1.24 to −0.35, p = 0.0005) was statistically significant at 6 months, in favor of aPDT. In these RCTs, aPDT was unable to demonstrate efficacy in reducing the microbial species associated with periodontitis. aPDT as an adjuvant to SRP improves the PD reduction and CAL gain more effectively than only SRP. RCTs are needed to establish standardized protocols with longer follow-up times in order to provide more results on aPDT adjunctive to SRP in smokers with periodontitis.
Keywords: periodontitis; photodynamic therapy; smokers; ּscaling root planning